2014
DOI: 10.1167/iovs.13-13825
|View full text |Cite
|
Sign up to set email alerts
|

Foveal Sparing in Stargardt Disease

Abstract: Foveal sparing occurs mainly in patients with late-onset STGD1 and represents the milder end of the clinical spectrum in STGD1. The anatomy, metabolism, and biochemistry of the retina, as well as genetic variations in genes other than ABCA4, can influence the etiology of foveal sparing. Identifying these fovea-protecting factors will facilitate the future development of strategies designed to treat STGD1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 53 publications
4
61
0
2
Order By: Relevance
“…Cases with extensive widespread atrophy with concomitant foveal sparing have also been described, though less frequently. 18,27,28 Foveal sparing was not evaluated in this cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Cases with extensive widespread atrophy with concomitant foveal sparing have also been described, though less frequently. 18,27,28 Foveal sparing was not evaluated in this cohort.…”
Section: Discussionmentioning
confidence: 99%
“…We assessed presence of foveal sparing, which we defined as RPE atrophy encircling a structurally and functionally (BCVA, ‡20/200) preserved fovea by ‡1808, 15 by evaluation of FAF and/or OCT.…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…[5][6][7][8][9][10] A combination of disease-causing ABCA4 alleles may, therefore, result in a severe, early-onset STGD1 phenotype (i.e., onset 10 years of age), 11,12 which is often observed as rapidly progressive cone-rod dystrophy, 5,13 in classical STGD1, 10 or in late-onset STGD1. [14][15][16] In about half of the patients with late-onset STGD1 (onset >44 years of age), only one disease-causing allele was identified, despite the sequence analysis of all coding variants. 16 In carriers of monoallelic ABCA4 variants, the second variant can reside in introns, outside of splice sites, not detected by standard sequencing methods.…”
mentioning
confidence: 99%
“…[9,20] The precise etiology of foveal sparing in STGD1 is unknown but certain theories point to the anatomical factors within this region that impart protective effects--for instance, given the damaging effects of light in the pathogenesis of STGD1[21,22] it has been suggested that the presence of luteal pigment, which absorbs short-wavelength and ultraviolet light, protects this region. [23] Another hypothesis points to the ability of cones to receive 11- cis -retinal from Muller cells enabling the alternative visual cycle, whereas the chromophore in rods is solely derived from the RPE cells which have been found to be significantly affected in STGD1.…”
Section: Discussionmentioning
confidence: 99%